A Walk to the Cherwell River Meadows: (Meaningfulness and) the Perceivable Form of the Urban Landscape - de Wit, Saskia (Writingplace, 2022)
In order to generate insights on the role of perceivable form, this article presents an excursion to Oxford, a mid-size European city with a strong urban identity. By weaving the landscape of the non-traditional architectural ensemble of St Catherine’s College into that of the traditional urban landscape, this paper aims to unfold (the perception of) the physical landscape, beyond the polemics of architectural style, as a generator of meaningfulness. Devoid of the style characteristics that determine our mental image of Oxford but remaining loyal to the programmatic and compositional logic of the Oxford colleges, the ensemble exposes just how much the quality of the physical landscape can affect